Polycyclic aromatic hydrocarbons (PAH) in Portuguese educational settings: a comparison between preschools and elementary schools - Slezakova, Klara (2019)
The aim of this study was to determine levels and risks due to inhalation exposure to polycyclic aromatic hydrocarbons (PAH) in different educational settings, namely for 3- to 5- year-old and 6- to 10-year-old children. Eighteen PAH (16 priority designated by US Environmental Protection Agency (USEPA) and dibenzo[a,l]pyrene and benzo[j]fluoranthene) were simultaneously collected in indoor and outdoor air at two Portuguese preschools (PS1-PS2) and five elementary schools (ES1-ES5) from March to May 2014. Indoor concentrations at PS and ES were significantly different, with total levels (∑PAHs) 0.721-15.9 ng/m3 at PS1-PS2 and 5.03-23.6 ng/m3 at ES1-ES5. The corresponding outdoor concentrations were, respectively, 1.22-32.7 ng/m3 and 2.6-31.5 ng/m3. Polycyclic aromatic hydrocarbons with 2-3 aromatic rings were predominantly emitted by indoor sources, while compounds with 4-6 aromatic rings were mainly generated by infiltration of ambient PAH pollution to indoors. Excess lifetime risks of lung cancer exceeded the World Health Organization (WHO) designated guideline of 10-5 in both types of schools (15-42-fold at PS; 15-52-fold at ES). However, total (sum of indoor and outdoor exposure) incremental lifetime cancer risks (ILCR) were below the USEPA level of 10-6 at all studied institutions and thus considered negligible. Finally, ILCR due to indoor exposure represented 60-75% and 70-85% of the total ILCR at PS and ES, respectively, thus indicating the need for development and implementation of indoor air quality guidelines in educations settings.